The Literature Review of Palliative Care Interventions for Surgical Patients - Stephanie, Stephanie; I Putu Gede Dharma Eka, I Putu Gede Dharma Eka (The Indonesian Journal of General Medicine, 2024)
Background: The integration of palliative care into surgical settings has gained increasing attention in recent years, reflecting a growing recognition of the importance of addressing patients' holistic needs throughout the surgical continuum. Literature Review: The reviewed literature highlights a significant shift in professional beliefs regarding the implementation of palliative care alongside surgical interventions, suggesting that such integration can enhance patient outcomes and quality of life. The efficacy of preoperative psychological interventions is also examined, revealing short-term benefits but insufficient evidence regarding long-term outcomes. Finally, the prognostic determinants of health in cancer patients requiring emergency surgical consultation are investigated, emphasizing the role of early palliative care involvement in improving symptom management and potentially prolonging life. Conclusion: In conclusion, the integration of palliative care interventions within surgical contexts is essential for addressing the holistic needs of patients. The literature consistently advocates for early involvement of palliative care teams, the incorporation of spiritual and psychological support, and the establishment of structured protocols to enhance patient outcomes. These findings underscore the necessity of a paradigm shift in surgical practice that embraces palliative care as a core component of patient management.